Light Guidance Control of Human Drivers: Driver Modeling, Control System Design, and VR Experiment. Issue 41 (2022) - Takeda, M.; Inoue, M.; Fang, X.; Minami, Y.; Maestre, J.M.
Abstract: This paper addresses light guidance control for human-driven vehicles. We manipulate pace-making-light (PML) installed in the road environment to make drivers accelerate their vehicles unconsciously. Also, since the performance of the control system relies on the human reaction, we address the modeling of the driver's behavior guided by PML. To this end, we tested human subjects by using a driving simulator developed in a virtual reality environment. The collected data were used to model the driver's behavior and to perform a PML control simulation. In particular, the driver model is utilized for the design of a model predictive controller that is implemented as the PML logic.